Association between naturally occurring lithium in drinking water and suicide rates: systematic review and meta-analysis of ecological studies. (December 2020) - Memon, Anjum; Rogers, Imogen; Fitzsimmons, Sophie M. D. D.; Carter, Ben; Strawbridge, Rebecca; Hidalgo-Mazzei, Diego; Young, Allan H.
Abstract : Background: The prevalence of mental health conditions and national suicide rates are increasing in many countries. Lithium is widely and effectively used in pharmacological doses for the treatment and prevention of manic/depressive episodes, stabilising mood and reducing the risk of suicide. Since the 1990s, several ecological studies have tested the hypothesis that trace doses of naturally occurring lithium in drinking water may have a protective effect against suicide in the general population. Aims: To synthesise the global evidence on the association between lithium levels in drinking water and suicide mortality rates. Method: The MEDLINE, Embase, Web of Science and PsycINFO databases were searched to identify eligible ecological studies published between 1 January 1946 and 10 September 2018. Standardised regression coefficients for total (i.e. both genders combined), male and female suicide mortality rates were extracted and pooled using random-effects meta-analysis. The study was registered with PROSPERO (CRD42016041375). Results: The literature search identified 415 articles; of these, 15 ecological studies were included in the synthesis. The random-effects meta-analysis showed a consistent protective (or inverse) association between lithium levels/concentration in publicly available drinking water and total (pooled β = −0.27, 95% CI −0.47 to −0.08; P = 0.006, I 2 = 83.3%), male (pooled β = −0.26, 95% CI −0.56 to 0.03; P = 0.08, I 2 = 91.9%) and female (pooled β = −0.13, 95% CI −0.24 to −0.02; P = 0.03, I 2 = 28.5%) suicide mortality rates. A similar protective association was observed in the six studies included in the narrative synthesis, and subgroup meta-analyses based on the higher/lower suicide mortality rates and lithium levels/concentration. Conclusions: This synthesis of ecological studies, which are subject to the ecological fallacy/bias, supports the hypothesis that there is a protective (or inverse) association between lithium intakes from public drinking water and suicide mortality at the population level. Naturally occurring lithium in drinking water may have the potential to reduce the risk of suicide and may possibly help in mood stabilisation, particularly in populations with relatively high suicide rates and geographical areas with a greater range of lithium concentration in the drinking water. All the available evidence suggests that randomised community trials of lithium supplementation of the water supply might be a means of testing the hypothesis, particularly in communities (or settings) with demonstrated high prevalence of mental health conditions, violent criminal behaviour, chronic substance misuse and risk of suicide.